2015
DOI: 10.1140/epjb/e2015-50742-1
|View full text |Cite
|
Sign up to set email alerts
|

Towards real-world complexity: an introduction to multiplex networks

Abstract: Many real-world complex systems are best modeled by multiplex networks of interacting network layers. The multiplex network study is one of the newest and hottest themes in the statistical physics of complex networks. Pioneering studies have proven that the multiplexity has broad impact on the system's structure and function. In this Colloquium paper, we present an organized review of the growing body of current literature on multiplex networks by categorizing existing studies broadly according to the type of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
112
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(115 citation statements)
references
References 176 publications
(369 reference statements)
0
112
0
Order By: Relevance
“…Multilayer networks [1][2][3] describe complex systems formed by different interacting networks. Examples of multilayer networks are ubiquitous, ranging from infrastructures and transportation networks to cellular and brain networks [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Multilayer networks [1][2][3] describe complex systems formed by different interacting networks. Examples of multilayer networks are ubiquitous, ranging from infrastructures and transportation networks to cellular and brain networks [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…where σ k [α] is the standard deviation of degrees in layer 30 α [15,29]. The value of this Pearson correlation coefficient 31 between the two layers is r = 0.271, which indicates weak 32 positive correlation [21].…”
mentioning
confidence: 99%
“…20,21 Several researches have shown that the topological features of a layer are indeed a®ected by the shape of other layers in multiplex networks. 18,19,22 In other words, the traditional link prediction methods only take into account the topological information derived from the single-layer networks (called the intralayer information) but neglect the additional information originated from other layers in multiplex networks (called the interlayer information). From the macroperspective point of view, if a multiplex network is treated as an integrated network, the interactions between nodes in di®erent layers can be regarded as the overall structural features of these nodes in di®erent aspects.…”
Section: Introductionmentioning
confidence: 99%